THE SEMANTICS OF STYLISTIC DEVICES OF HYPERBOLE/MEIOSIS IN ENGLISH AND UZBEK PHRASEOLOGY - Sagdullayeva, Feruza (Innovative Development in Educational Activities, 2022)
This article deals with the importance of stylistic devices in the English and Uzbek languages including, lexical stylistic devices of Hyperbole and Meiosis and their semantic features while using as the core elements of phraseology. Understanding semantic features of the stylistic devices of Hyperbole and Meiosis can help speakers to make their speeches more colorful and emotional.